2020
DOI: 10.1186/s13071-020-3965-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomic and mass spectrometric analysis of Eimeria acervulina antigens recognized by antisera from chickens infected with E. acervulina, E. tenella or E. necatrix

Abstract: Background: Coccidiosis is caused by Eimeria spp. and can result in severe economic losses to the global poultry industry. Due to anticoccidial drug resistance rapidly developing in the parasites and drug residues in poultry products, efficacious and safe alternative coccidia control measures are needed. The objective of the present study was to identify common protective antigens which may be used as vaccine candidates in the development of subunit, multivalent, cross-protective vaccines against most of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Antiserum-based immunoproteomic studies have been carried out for identifying such potential antigens from several parasites including ectoparasites. 25,26 Initially, the A siamensis parasite species was identified by PCR and maintained in wet laboratory on rohu as a host for our experiments. We developed immune serum in rohu to probe Argulus antigens in Western blot transferred from the 2D gel to identify the immunoreactive proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Antiserum-based immunoproteomic studies have been carried out for identifying such potential antigens from several parasites including ectoparasites. 25,26 Initially, the A siamensis parasite species was identified by PCR and maintained in wet laboratory on rohu as a host for our experiments. We developed immune serum in rohu to probe Argulus antigens in Western blot transferred from the 2D gel to identify the immunoreactive proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on coccidial antigens have mostly identified a variety of common antigens and proteins, but they have been mostly limited to chicken coccidiosis; only E. stiedai has been previously studied in rabbits (Song et al, 2017). Liu et al (2020) identified twenty-one Eimeria acervulina sporozoite antigens that can be recognised by antisera from chickens infected with E. acervulina, E. tenella or E. necatrix. Studies in chickens and our results support the need for further comparisons of coccidial antigens parasitising rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Over many decades, Eimeria vaccines have gained a considerable importance, by virtue of effectively preventing the disease without developing resistance in field strains as in anticoccidial chemotherapeutics (Sander et al 2019 ; Liu et al 2020 ; Zhao et al 2020 ). Rather, the sensitivity towards previously resistant chemical anticoccidials has been enhanced by the use of Eimeria vaccines (Jenkins et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%